La construcción de la figura de Rafael Correa en los medios de comunicación impresos diario El Universo y El Expreso - Espinoza Briones, Rubí Zulay (2019)
The present case study aims to investigate the treatment of the news about the construction of the figure of Rafael Correa in the print media newspaper El Universo and El Expreso, in the development of the same the influence of the treatment that was He gave the news in said newspapers and his influence in the construction of said figure, during the process that lasted his mandates and subsequent to his mandate. For the development of the present case study, the non-experimental design is considered, with a qualitative approach, with an analytical - inductive method, with a type of documentary research, since random publications will be collected between 2007 and 2019 regarding Rafael Correa of the newspapers El Universo and El Expreso, which is complemented with techniques such as: Observation and interview, concluding that the construction of Rafael Correa's figure was an accelerated process before his election as President of the Republic, since since his departure from the Ministry of Economy and Finance, the figure has already been outlined and he is satisfied with the fulfillment of the social campaign proposals upon reaching the presidency